2016
DOI: 10.1007/s11274-016-2142-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a natural soil salinity gradient on fungal endophytes in wild barley (Hordeum maritimum With.)

Abstract: Occurrence and distribution pattern of fungal endophytes in different tissues of halophytic plants across saline depressions are poorly studied. We investigated the endophytic fungal communities inhabiting roots, stems and leaves of Hordeum maritimum collected in a soil salinity gradient, i.e. non-saline, slightly saline and saline, using a culture-dependent approach. A total of 20 taxa belonging to Ascomycota phylum were identified by ITS rRNA gene sequence. Pyronema domesticum and Alternaria spp. were the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Previous studies showed that genera such as Fusarium, Penicillium, Trichoderma, Aspergillus and Rhodotorula revealed in this study also occur in other cultivated soybean plants ( Impullitti and Malvick, 2013 ; Pimentel et al., 2006 ; Russo et al., 2016 ; Fernandes et al., 2015 ; de Souza Leite et al., 2013 ). The fungal endophytic communities of barley were represented by such genera as Fusarium, Penicillium, Metarhizium, Trichoderma, Rhodotorula, Metschnikowia, and Cryptococcus, which is consistent with previous studies of other authors ( Murphy et al, 2015, 2018; Hammami et al., 2016 ). Species of the genera Beauveria, Aureobasidium, Metschnikowia and Cryptococcus as endophytic fungi were not found in soybean and barley in previous studies and were isolated from these plants for the first time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies showed that genera such as Fusarium, Penicillium, Trichoderma, Aspergillus and Rhodotorula revealed in this study also occur in other cultivated soybean plants ( Impullitti and Malvick, 2013 ; Pimentel et al., 2006 ; Russo et al., 2016 ; Fernandes et al., 2015 ; de Souza Leite et al., 2013 ). The fungal endophytic communities of barley were represented by such genera as Fusarium, Penicillium, Metarhizium, Trichoderma, Rhodotorula, Metschnikowia, and Cryptococcus, which is consistent with previous studies of other authors ( Murphy et al, 2015, 2018; Hammami et al., 2016 ). Species of the genera Beauveria, Aureobasidium, Metschnikowia and Cryptococcus as endophytic fungi were not found in soybean and barley in previous studies and were isolated from these plants for the first time.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the number of isolates from aboveground organs was less comparable to underground ones. Similar results were obtained from studies on other grassy plant species ( Ghimire et al., 2011 ; Wearn et al., 2012 ; Jin et al., 2013 ), including barley ( Hammami et al., 2016 ). Such differences in the distribution of endophytes in parts of plants can be explained by several reasons.…”
Section: Discussionsupporting
confidence: 86%
“…Analysis of four plant species growing across environmental gradients in different geographic locations revealed a dynamic ecological process that occurs between plants and fungal symbionts based on soil chemistry and plant fitness needs ( Figure 1 , Table 1 ). This is in line with other studies indicating that changes in soil chemistry along a chemical gradient can alter fungal endophyte associations within a single plant species (Maciá-Vicente et al, 2012 ; Glynou et al, 2016 ; Hammami et al, 2016 ; Kia et al, 2018 ). The interplay between endophyte conferred benefits and plant fitness appears to be a significant driver in plant niche expansion ( Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…It is now clear that the ecology and adaptive potential of plants is driven, at least in part, by microbial symbionts. This is best represented by the symbiotic dynamics observed in plants growing across environmental gradients (Maciá-Vicente et al, 2012 ; Ranelli et al, 2015 ; Glynou et al, 2016 ; Hammami et al, 2016 ; Kia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…H. marinum, also known as seaside barley, is a true halophile species present in Tunisian saline depressions having a soluble Na + content of about 90 µmol g −1 soil (ECe of 19.0 dS m −1 ), corresponding to about 200 mM [76]. In these salt-affected ecosystems, this species significantly contributes to annual biomass production and results very useful for fodder production, like sorghum in arid areas of Iran [77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%